Simulation study of thermally initiated rail defects. (February 2014) - Scott, D; Fletcher, DI; Cardwell, BJ
Ultrasonically detected 'squat-type' rail defects are becoming increasingly common on railways throughout the world. On the London Underground (LU) these defects are found on three lines. Focussing on the difference between these lines and others on the LU network has identified vehicles with modern AC traction characteristics as a common theme found only on problem lines. Metallurgical analysis of the defects found that the mechanisms for generation and growth are not consistent with conventional rolling contact fatigue, with evidence of significant thermal input. The defects are only found on open sections. The areas most susceptible to the defects are those where low-speed running is more common. A mathematical model of the traction package has been used to examine the forces and thermal input generated at the wheel–rail interface with modern wheel-spin control systems under wheel slip and adhesion recovery conditions. The outputs have been analysed to assess whether sufficient forces and temperatures are generated to explain the observed rail damage. The results suggest that under certain circumstances wheel-spin recovery generates sufficient rail surface energy for martensitic transformation. Additional modelling suggests that thermal input from wheel-spin aids crack propagation and that regions of slightly degraded (wet as opposed to leaf or oil contaminated) rail adhesion are sufficient to initiate these flaws.